2002
DOI: 10.1093/brain/awf201
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of group II heteronymous pathways is enhanced in rigid lower limb of de novo patients with Parkinson's disease

Abstract: A potent heteronymous excitation of quadriceps motoneurones via common peroneal group II afferents has recently been demonstrated in normal subjects. The aim of this study was to investigate whether this group II excitation contributes to rigidity in Parkinson's disease. The early and late facilitations of the quadriceps H reflex elicited by a conditioning volley to the common peroneal nerve (CPN) at twice motor threshold, attributed to non-monosynaptic group I and group II excitations, respectively, were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…Our observation of an elevated LLSR (Figure 2) combined with no change in prevalence or magnitude of stretch-evoked neuronal responses in PTNs is consistent with the view that the alteration in reflex function that mediates the exaggerated LLSR of PD is localized to the spinal cord (Simonetta Moreau et al, 2002; Marchand-Pauvert et al, 2011; Raoul et al, 2012). Several abnormalities in segmental function have been observed in PD and there is no consensus as to which of them contribute most significantly to the LLSR or rigidity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our observation of an elevated LLSR (Figure 2) combined with no change in prevalence or magnitude of stretch-evoked neuronal responses in PTNs is consistent with the view that the alteration in reflex function that mediates the exaggerated LLSR of PD is localized to the spinal cord (Simonetta Moreau et al, 2002; Marchand-Pauvert et al, 2011; Raoul et al, 2012). Several abnormalities in segmental function have been observed in PD and there is no consensus as to which of them contribute most significantly to the LLSR or rigidity.…”
Section: Discussionsupporting
confidence: 86%
“…For all of these, dysfunction within the BG may affect segmental motor function via descending BG projections to the pedunculopontine nucleus and from there to spinal cord projecting brainstem nuclei (Delwaide et al, 2000). Degeneration of the noradrenergic projection to the spinal cord may also play an important role (Simonetta Moreau et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been shown that limb rigidity in patients with PD points to sensorimotor processing damage resulting from a change in their descending monoaminergic inhibitory control [42], we sought to determine the effect of a pro-parkinsonian neurotoxin on the diencephalospinal pathway despite the absence of DAT expression.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of evidence of group II excitation from quadriceps to soleus in healthy subjects may result from concomitant effects of the recurrent inhibition. In stroke individuals, the increase of group II excitation would probably affect mostly the first part of the inhibition since it has been demonstrated that group II afferents normally have their peak influence from 6 to 20 ms after the onset of the early group I induced facilitation [22], [53], [54], [55]. Our results suggest that recurrent inhibition could also be impaired in itself since the inhibition is reduced at the late ISIs (30 ms and 40 ms ISI) at which the influence of group II excitation must be diminished.…”
Section: Discussionmentioning
confidence: 99%